Long-range Fourier domain optical coherence tomography of the pediatric subglottis. Issue 2 (February 2015) - Volgger, Veronika; Sharma, Giriraj K.; Jing, Joseph C.; Peaks, Ya-Sin A.; Loy, Anthony Chin; Lazarow, Frances; Wang, Alex; Qu, Yueqiao; Su, Erica; Chen, Zhongping; Ahuja, Gurpreet S.; Wong, Brian J.-F.
Abstract Background Acquired subglottic stenosis (SGS) most commonly results from prolonged endotracheal intubation and is a diagnostic challenge in the intubated child. At present, no imaging modality allows for in vivo characterization of subglottic microanatomy to identify early signs of acquired SGS while the child remains intubated. Fourier domain optical coherence tomography (FD-OCT) is a minimally invasive, light-based imaging modality which provides high resolution, three dimensional (3D) cross-sectional images of biological tissue. We used long-range FD-OCT to image the subglottis in intubated pediatric patients undergoing minor head and neck surgical procedures in the operating room. Methods A long-range FD-OCT system and rotary optical probes (1.2 mm and 0.7 mm outer diameters) were constructed. Forty-six pediatric patients (ages 2–16 years) undergoing minor upper airway surgery (e.g., tonsillectomy and adenoidectomy) were selected for intraoperative, trans-endotracheal tube FD-OCT of the subglottis. Images were analyzed for anatomical landmarks and subepithelial histology. Volumetric image sets were rendered into virtual 3D airway models in Mimics software. Results FD-OCT was performed on 46 patients (ages 2–16 years) with no complications. Gross airway contour was visible on all 46 data sets. Twenty (43%) high-quality data sets clearly demonstrated airway anatomy (e.g., tracheal rings, cricoid and vocal folds) and layered microanatomy of the mucosa (e.g., epithelium, basement membrane and lamina propria). The remaining 26 data sets were discarded due to artifact, high signal-to-noise ratio or missing data. 3D airway models were allowed for user-controlled manipulation and multiplanar airway slicing (e.g., sagittal, coronal) for visualization of OCT data at multiple anatomic levels simultaneously. Conclusions Long-range FD-OCT produces high-resolution, 3D volumetric images of the pediatric subglottis. This technology offers a safe and practical means for in vivo evaluation of lower airway microanatomy in intubated pediatric patients. Ultimately, FD-OCT may be applied to serial monitoring of the neonatal subglottis in long-term intubated infants at risk for acquired SGS.